2018
DOI: 10.1515/ijnsns-2017-0224
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a Predator–Prey Model with Holling Type II Functional Response Incorporating a Prey Refuge Depending on Both the Species

Abstract: We propose a mathematical model for prey–predator interactions allowing prey refuge. A prey–predator model is considered in the present investigation with the inclusion of Holling type-II response function incorporating a prey refuge depending on both prey and predator species. We have analyzed the system for different interesting dynamical behaviors, such as, persistent, permanent, uniform boundedness, existence, feasibility of equilibria and their stability. The ranges of the significant parameters under whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 42 publications
1
11
0
1
Order By: Relevance
“…The parameter k 1 represents half-saturation constant of predation. Holling type II functional response is more realistic than Holling type I because the rate of the prey predation is saturated [23]. This is in accordance with the real conditions, that it is impossible to predators to eat the prey continuously.…”
Section: If In Model (supporting
confidence: 60%
“…The parameter k 1 represents half-saturation constant of predation. Holling type II functional response is more realistic than Holling type I because the rate of the prey predation is saturated [23]. This is in accordance with the real conditions, that it is impossible to predators to eat the prey continuously.…”
Section: If In Model (supporting
confidence: 60%
“…In this study, we have considered x, y as the prey and predator species respectively and δxy as the amount of nonlinear prey refuge (cf. [17,[19][20][21]) admissible for t 0 with 0 x(1 − δy) x. The factor y y+h comes into predator growth function to decrease the predator growth rate because, if a predator eats more, it will be less likely to die from starvation or from the consequences of weakness due to hunger; and it is positive for any value of functional response, because a predator is highly unlikely to live forever.…”
Section: Model Compositionmentioning
confidence: 99%
“…Biological description and dimension of the parameters used in the model (2.3) have been chosen from[19] and[21]: V stands for volume of the species and T for time.…”
mentioning
confidence: 99%
“…Santra et al [15] investigated the dynamical actions with Crowley-Martin functional response-associated prey refuge. Finally, Molla et al [16] suggested a model for Holling type-II prey-predator interactions in a prey refuge. In this paper, a Lotka-Volttera food web model with a prey refuge that consists of prey and predator is proposed and studied.…”
Section: Jaber and Bahloolmentioning
confidence: 99%